An Analysis on Core Competencies of Successful Sellers: Exploring the Impact of Core Competencies on Sales Performance (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Sales competencies for sales executives are shared over the business group so as to deliver the best representatives skills. These core competencies range each job on the business group, from representatives to director. This paper analyses the sales competencies with sales performance.